2005
DOI: 10.1182/blood-2005-04-1450
|View full text |Cite
|
Sign up to set email alerts
|

The E3 ubiquitin-protein ligase Triad1 inhibits clonogenic growth of primary myeloid progenitor cells

Abstract: IntroductionGranulocytes and monocytes develop from common myeloid progenitor cells through a complex network of cell growth, differentiation, and apoptosis-regulating factors. Alterations in these processes may cause acute myeloid leukemia, which is characterized by uncontrolled proliferation of immature myeloid cells that fail to differentiate toward mature functional cells. 1,2 In leukemia, mutations occur in genes encoding tyrosine kinases such as Fms-like tyrosine kinase 3 (Flt3), c-kit, neuroblastoma ras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
80
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(83 citation statements)
references
References 55 publications
3
80
0
Order By: Relevance
“…18,20 BRE QPCR and MLL-AF9 fusion gene detection BRE expression was measured by QPCR on cDNA samples using a commercially available primer/probe set (Applied Biosystems; Hs01046283_m1), and data were normalized by PBGD or ␤-ACTIN quantitative PCR (QPCR). 22 MLL-AF9 breakpoint PCR on the cohort of 525 patients was performed as described previously. 23,24 For the validation cohort, conventional chromosome banding and FISH for MLL-AF9 translocations were performed as previously described.…”
Section: Cell Isolationmentioning
confidence: 99%
“…18,20 BRE QPCR and MLL-AF9 fusion gene detection BRE expression was measured by QPCR on cDNA samples using a commercially available primer/probe set (Applied Biosystems; Hs01046283_m1), and data were normalized by PBGD or ␤-ACTIN quantitative PCR (QPCR). 22 MLL-AF9 breakpoint PCR on the cohort of 525 patients was performed as described previously. 23,24 For the validation cohort, conventional chromosome banding and FISH for MLL-AF9 translocations were performed as previously described.…”
Section: Cell Isolationmentioning
confidence: 99%
“…Co-overexpression of Triad1 and UbcH7 increases total protein ubiquitination in myeloid progenitor cells or myeloid cell lines, but genuine Triad1/UbcH7 substrate proteins have not been identified (20). Although Triad1 is ubiquitously expressed, expression increases during myelopoiesis and is greatest in mature neutrophils (19). Other investigators found that engineered overexpression of Triad1 in myeloid progenitor cells results in decreased colony formation (19).…”
mentioning
confidence: 99%
“…The E3 ligase attaches ubiquitin to the substrate, thereby tagging the substrate for proteasomemediated degradation. Previous studies determined that Triad1 interacts functionally with several E2 ligases, including Ubch7 and Ubc13 (19,20). Co-overexpression of Triad1 and UbcH7 increases total protein ubiquitination in myeloid progenitor cells or myeloid cell lines, but genuine Triad1/UbcH7 substrate proteins have not been identified (20).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…35 Another member of the TRIAD family of E3 ligases, Triad3, was shown to catalyze the ubiquitylation of the Toll-like receptors TLR4 and 9. This results in the proteasomal degradation of these receptors.…”
Section: Nf-jb Signaling: An Example Of An Ups-regulated Pathwaymentioning
confidence: 99%